Potensi Rempah-Rempah sebagai Bahan Pembuatan Minyak Balur - Purba, Intan Sabila Putri; Rezky, Deswita Ina; Samio, Samio (IAI Nasional Laa Roiba Bogor, 2024)
As the villagers of Bandar Kuala become more knowledgeable about healthy lifestyles, the need for locally available herbal medicines with health benefits is bound to increase. Some of the sources of ingredients from spices and plants that are easily accessible to Bandar Kuala villagers and have various health benefits are turmeric, cardamom, bay leaves, soursop leaves, candlenut, sambiloto, frangipani flowers, kenanga flowers, anise, areca flowers, kencur, coconut oil, coriander, nutmeg, cloves, lempuyang wangi, temu mango, temu kunci. Phytochemicals from these plants are known to prevent or cure various diseases such as high blood pressure, cancer, diabetes, flu, cough, sore throat, pain and others. Cultivation of traditional medicinal plants in the garden on a large scale can be of economic value to the community, thus potentially improving the welfare of the villagers, and it is important to provide health education on the use of spices that already exist in an environment that is easily accessible to the residents of Bandar Kuala village.